2012
DOI: 10.4028/www.scientific.net/kem.531-532.250
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Characterization of Zinc and Magnesium Doped Hydroxyapatite

Abstract: Zn or Mg ions doped hydroxyapatite (HA) particles were successfully developed by introducing various concentration of Zn or Mg in the starting solution using wet chemical precipitation method and followed a hydrothermal treatment. The products were identified as HA by XRD and FTIR, and the precipitated particles had a rod-like morphology. All the products for Mg and Zn ions concentration in the preparation solution less than 40 mol% were identified as HA. Substitution of Mg and Zn in HA crystal would impair th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Substitution of Mg in HA crystals obviously reduced the crystallinity of HA whiskers and both the a and c values of HA unit cell, especially for that of HA crystals doped with ≥ 8 % Mg, which was coincident with the previous reports [19,20]. However, the changes in the lattice parameters for Zn doped HA did not show any regularity, the a value increased when the doping concentration was > 5 %, but the c value nearly remained a constant value, which was consistent with the finding of Miyaji [16], who reported that the lattice parameter a decreased up to 5 mol.…”
Section: Lattice Parameterssupporting
confidence: 73%
See 1 more Smart Citation
“…Substitution of Mg in HA crystals obviously reduced the crystallinity of HA whiskers and both the a and c values of HA unit cell, especially for that of HA crystals doped with ≥ 8 % Mg, which was coincident with the previous reports [19,20]. However, the changes in the lattice parameters for Zn doped HA did not show any regularity, the a value increased when the doping concentration was > 5 %, but the c value nearly remained a constant value, which was consistent with the finding of Miyaji [16], who reported that the lattice parameter a decreased up to 5 mol.…”
Section: Lattice Parameterssupporting
confidence: 73%
“…With the increase of Mg or Zn concentration in the initial synthesis solution, both the length and aspect ratio were impaired. For the proportion of Mg ions of > 15 %, few second phases appeared in the products, they were identified as Ca 19 13.80 . Therefore, the appropriate starting concentration of these ions in HA whiskers should be less than 10 mol.…”
Section: Lattice Parametersmentioning
confidence: 99%
“…Few studies have focused on the carbonate asymmetric stretching region of the IR spectra of Zn or Mg-doped apatites. Peaks obtained during characterization of Zn apatites include those at 1416 and 1465 cm −1 for an apatite with 0.01 mole Zn relative to 9.99 mole calcium (Fadeeva et al, 2012), peaks at 1429 and 1454 cm −1 for both Mg-and Zn-doped apatites with ∼5% dopant (Zhang et al, 2013), and peaks in the regions 1430-1433 cm −1 and 1458-1468 cm −1 for fluorapatites containing a 1:3 mole ratio of Mg to Ca (Peld et al, 1994). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic HA has been gradually accepted and widely used to repair bone and tooth defects due to its similarity with the composition of human hard tissue [1,2].…”
Section: Introductionmentioning
confidence: 99%